STUDENTS’ PERCEPTION ON DEVELOPING ENGLISH SPEAKING ABILITY THROUGH ONLINE ENGLISH FOR PRESENTATION CLASS - Arni Sukmiarni (Jurnal Sastra - Studi Ilmiah Sastra, 2023)
This study discusses Students’ Perception on developing English speaking Skill through Online English for Presentation Class. The study aims to investigate the students’ perception on the use of voice, the presentation structure and signposting in English for Presentation Class. The data used in this study were collected from students’ perception on their experience during their engagement in English for Presentation conducted in an online class. The participants involved as the participants in this study were those taking online English III as a compulsory subject course in a private higher educational institution in Bandung Indonesia. The results show that all students have positive perception towards the employment of using voice—word stress, sentence stress, intonation, chunking—the presentation structure, and signposting. Furthermore, through English for Presentation Class, students who still have low level of English speaking ability perceive positively that the practice of these activities help them develop their English Speaking ability and conducting an online class for English Presentation still receives good responses from the students.